2019
DOI: 10.1371/journal.pntd.0007330
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequence of Vibrio cholerae directly from dried spotted filter paper

Abstract: Background Global estimates for cholera annually approximate 4 million cases worldwide with 95,000 deaths. Recent outbreaks, including Haiti and Yemen, are reminders that cholera is still a global health concern. Cholera outbreaks can rapidly induce high death tolls by overwhelming the capacity of health facilities, especially in remote areas or areas of civil unrest. Recent studies demonstrated that stool specimens preserved on filter paper facilitate molecular analysis of Vibrio ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…It enables phylogenetic trees to be quickly reconstructed from a large number of genomes without the burden of multiple sequence alignments (see e.g. 2,29, [44][45][46][47][48][49][50][51][52]. This report confirms this view by showing that proper evolutionary distances can be easily derived from MH p-distance estimates, therefore enabling accurate phylogenetic inferences.…”
Section: Discussionsupporting
confidence: 63%
“…It enables phylogenetic trees to be quickly reconstructed from a large number of genomes without the burden of multiple sequence alignments (see e.g. 2,29, [44][45][46][47][48][49][50][51][52]. This report confirms this view by showing that proper evolutionary distances can be easily derived from MH p-distance estimates, therefore enabling accurate phylogenetic inferences.…”
Section: Discussionsupporting
confidence: 63%
“…Other than sequencing costs, one of the barriers to generating V. cholerae whole genome sequences is heterogeneity in the sample types available; sequencing typically requires relatively large amounts of purified nucleic acid, and is therefore often not attempted when only crude specimens (as opposed to cultured isolates) are available. Previous studies have shown that V. cholerae sequencing from Alkaline Peptone enriched (APW) stool or isolates on filter paper can be successful 26 , so we attempted to take this one step further, comparing the success of various specimen types preserved on filter paper across samples from several countries and using different nucleic acid extraction techniques. Specifically, we compared sequencing from bacterial cultures, bacterial isolates preserved on filter paper, and whole stool directly spotted onto filter paper.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we aimed to fill some of the gaps in our understanding of 7PET V. cholerae O1 circulation in Southeast Africa using isolates collected from 2007–2018 in Uganda, Kenya, Tanzania, Malawi, and Zambia. In addition, we explored the potential of performing whole genome sequencing from low-cost sample preservation methods (e.g., stool or isolates on filter paper), which facilitates specimen collection in resource-constrained areas where isolates would otherwise not be captured 18,26 . We found that sequencing from these samples can produce whole genome sequences, which we used to identify multiple co-circulating V. cholerae lineages in Southeast Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the new generation of tests should help clinicians to decide on appropriate antibiotic use in a context of growing concern of antimicrobial resistance. Furthermore, as we rely more on genomics for the classification of circulating V. cholerae strains, more work is needed to understand whether the RDTs used could serve as an appropriate medium to temporarily preserve and transport the genetic material needed for subsequent molecular analyses, as has been done with filter paper [ 14 ].…”
Section: Further Research On Rdtsmentioning
confidence: 99%